Occlusal Analysis and Management of a Patient with Median Nerve Palsy of Unknown Etiology: A Case Report - Torii, Kengo (British Journal of Healthcare and Medical Research, 2023)
A patient presented with a diagnosis of median nerve palsy in the fingers of the right hand of unknown etiology by an orthopedic surgeon. Occlusal analysis showed that the habitual occlusal position and the muscular position were inconsistent, and in the muscular position the left second premolars were in premature contact. When the biting force was examined, it was mean 37 kg for the right and mean 13.3 kg for the left at first visit. The left-right difference in bite force was significant (p<0.005). As a result of five times of occlusal adjustment, occlusal contact of both molars was obtained, and the occlusal force was mean 20 kg on the right and mean 21 kg on the left, and there was no left-right difference. The median nerve palsy of the right hand also disappeared. In this case, the bite force on the right side was abnormally stronger than that on the left side, and the trigeminal motor nucleus on the right side was abnormally excited. It was considered that the activity of the trigeminal spinal cord nucleus was suppressed, resulting in median nerve palsy.